Efecto de medidas preventivas sobre indicadores de riesgo de caries dental - Fajardo Santacruz, María Claudia; González Caicedo, María Ximena; Mafla Chamorro, Ana Cristina (Universidad y Salud, 2023)
Objective: The purpose of this study was to compare the effectiveness of preventive measures based on dental caries risk. Materials and Methods: A cohort of 157 subjects who assisted to Clínica Odontológica was enrolled in this 12 months experimental clinical investigation. Test group and control group were randomized to receive no risk-based prevention and risk based prevention. At the end of this study 63 individuals completed all of these procedures. The caries risk assessment was done through “Riesgograma”. Results: The 100% of children had a high risk. Caries risk factors, such as, presence of dental plaque, dental caries and carbohydrates intake were presented from 95.2% to 100%. The risk-based prevention was more effective than no risk-based prevention to control caries incidence, however this difference was statistically insignificant. Conclusion: The risk-based prevention may be a good device to control the caries incidence, although it is relevant to have a better understanding of caries risk indicators and risk-based prevention to plan future preventive treatments in under developed countries.